Analisis Ketersediaan dan Kebutuhan Air Bersih pada Masyarakat di Kecamatan Bangkala Kabupaten Jeneponto - Yuniar, Diva Auliya; Praja, Soemitro Emin; Burhanuddin, Fathurrahman (LOSARI : Jurnal Arsitektur Kota dan Pemukiman, 2025)
The avaibility and demand for clean water are crucial aspects of community life, particularly in the Bangkala District of Jenponto Regency, which features divers geographical conditions . This study aims to analyze the availability and demand for clean water in Bangkala District , focusing on the distribution of household connections (SR) and water consumption levels in each village and sub-district. The data used include population size, land area, and elevation og the villages. The analysis seeks to identify gaps between the availability and demand for clean water among the community. The findings indicate significant variations in water availability across the villages, with those situated at lower elevations tending to have better access to water. Conversely, villages at higher elevations face challenges in accsessing clean water. These findings are expected to serve as a basis for improving the clean water distribution system in Bangkala District to optimally meet community needs.